Environment-economic analysis of diesel, hybrid electric, plug-in hybrid electric trucks in China. (April 2023) - Xu, Feiyang; Crawford, Curran; Feng, Yanbiao; Lin, Zhenhong; Li, Shunxi
Abstract: This study analyzed the environment-economic performance of diesel, hybrid electric, and plug-in hybrid electric trucks with different hybridization factors and battery capacities by comparing the carbon dioxide emissions of the well-to-wheel stage and total cost of ownership from 2020 to 2040. Data were collected through literature research, field investigations, and prototype analysis of popular trucks in China. The impact of grid mix, diesel & charging prices, and battery energy density was explored by scenario analysis. The sensitivity of driving distances from 100 km to 800 km was determined. It was found that hybrid electric trucks with high hybridization factors perform best. In the future, plug-in hybrid electric trucks with large batteries will perform best over short distances. Conversely, plug-in hybrid electric trucks with small batteries will be the best for medium and long distances. This is mainly due to the increasing proportion of green electricity and decreasing charging prices.